Visual and refractive associations with falls after first-eye cataract surgery - Palagyi, A.; Morlet, Nigel; McCluskey, P.; White, A.; Meuleners, Lynn; Ng, Jonathon; Lamoureux, E.; Pesudovs, K.; Stapleton, F.; Ivers, R.; Rogers, K.; Keay, L. (Elsevier BV, 2017)
© 2017. Purpose: To clarify the effect of first-eye cataract surgery on the incidence of falls and identify components of visual function associated with fall risk. Setting: Eight public hospital eye clinics in Sydney, Melbourne, and Perth, Australia. Design: Prospective cohort study. Methods: The study recruited patients who had bilateral cataract, were aged 65 years or older, and were on public hospital cataract surgery waiting lists. Comprehensive assessments of vision, physical function, and exercise activity were performed before and after first-eye cataract surgery. Falls were reported prospectively for up to 2 years and associations with falls were assessed using generalized linear mixed models. Results: Of the 329 patients recruited, 196 (66.6%) completed first-eye surgery within the study period. First-eye cataract surgery reduced incident falls by 33% (adjusted incidence rate ratio 0.67; 95% confidence interval [CI], 0.49-0.92; P = .01). Poorer dominant-eye visual acuity was associated with falls during the study timeline (incidence rate ratio, 2.20; 95% CI, 1.02-4.74; P = .04). Patients with larger than a spherical equivalent of ±0.75 diopter change in the spectacle lens (operated eye) had a 2-fold greater incidence of falls in the period after first-eye cataract surgery than those with less or no change in lens power (incidence rate ratio, 2.17; 95% CI, 1.23-3.85; P = .008). Conclusions: First-eye cataract surgery significantly reduced incident falls. Major changes in the dioptric power of spectacle correction of the operated eye after surgery increased the fall risk. Cautious postoperative refractive management is important to maximize the benefit of cataract surgery as a fall-prevention measure.